Uso de cinza de olaria e composto orgânico de macrófita aquática na recuperação de solos degradados - Gaudêncio, Hiara Ruth da Silva Câmara (2016)
The intensification of human activity for economic purposes has caused environmental impacts increasingly significant, for example, the suppression of vegetation and as a result soil impoverishment. In this sense, this research aimed to evaluate the use of pottery ash and organic macrophyte compound in the recovery of degraded soils. Thus, the experiment was conducted in a greenhouse with experimental design in a factorial arrangement of 5x5, being five doses of the compound of water hyacinth and five doses of ash with three replications, where the volume of soil corresponded to 2 dm³ and ash doses corresponded to 0, 1, 3, 5 and 10% of the volume of each vessel and the water hyacinth compound at 0, 5, 10, 20 and 30%. After mixing the composition of soil, compound and gray equivalent to each treatment, these were placed in plastic vessels, incubated for 20 days and then held the transplanting of Jucá seedlings (Libidibia ferrea). On the occasion of collection, the plants were cut at ground level, dry in forced-air oven at 70° C to constant weight, weighed, crushed in a grinder to obtain the dry matter of shoot (MSPA) and they were subsequently mineralized by nitric digestion. In the extracts were determined the total content of Fe, Zn, Mn, Cu, Cd and Pb. After removal of the plants, the soil in each vessel was air dried, homogenised and a sample was removed for performing analysis of Fe, Zn, Mn, Cu, Cd and Pb. The addition of ash and compound doses contributed to the increase in pH, which consequently influenced the absorption of heavy metals by plants as well as in their growth